2021
DOI: 10.1039/d1nj00754h
|View full text |Cite
|
Sign up to set email alerts
|

BaTi(BO3)2: an excellent birefringent material with highly coplanar isolated [BO3] groups

Abstract: The material with a large birefringence is needed for the optical system, and borate is a good choice for excellent birefringent material. Herein, we report two borates BaMⅣ(BO3)2 (MⅣ =...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Considering the generally good agreements of calculated birefringence for simple borate crystals as shown in Table 1 and references [47][48][49][50][51][52][53][54][55][56] , the enhanced birefringence of the title compound must come from the distorted ScO 6 octahedral units. It is a consensus that distorted polyhedrons, especially d 0 octahedra, are able to contribute to a large part to birefringence in certain transition metal containing materials, called as SOJT effect, for example TiO 2 [31] , BaTiO 3 [57] and recently reported BaTi(BO 3 ) 2 [32] . In Ba 3 Sc 2 (BO 3 ) 4 , Sc with d 0 electronic state displays a distorted coordinated environment, verified by the electronic density map (see later).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the generally good agreements of calculated birefringence for simple borate crystals as shown in Table 1 and references [47][48][49][50][51][52][53][54][55][56] , the enhanced birefringence of the title compound must come from the distorted ScO 6 octahedral units. It is a consensus that distorted polyhedrons, especially d 0 octahedra, are able to contribute to a large part to birefringence in certain transition metal containing materials, called as SOJT effect, for example TiO 2 [31] , BaTiO 3 [57] and recently reported BaTi(BO 3 ) 2 [32] . In Ba 3 Sc 2 (BO 3 ) 4 , Sc with d 0 electronic state displays a distorted coordinated environment, verified by the electronic density map (see later).…”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent to similar other C3 distorted d 0 state cations, e. g. Nb 5 + in rhombohedral LiNbO 3 and Ti 4 + in BaTi(BO 3 ) 2 give much enhanced birefringence from their cubic O h symmetry. [32,36] Although the birefringence of Ba 3 Sc 2 (BO 3 ) 4 is still slightly smaller than that of commercial CaCO 3 crystal from mineral sources (experimental 0.171 @ 633 nm) [58] , the difficulty of practical crystal growth and the narrow transparency range (350-2300 nm) prevent the applications of calcite crystal in special aspects of UV and laser industries. The d 0 transition metals usually bring in a drawback of strong absorption in the ultraviolet (UV) region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Therefore, there are many strategies to design new birefringent crystal materials, including: (1) introducing planar π-conjugated groups ( e.g. , [BO 3 ], [B 3 O 6 ], [C 3 N 3 O 3 ] and [NO 3 ]); typical examples are Li 6 Zn 3 (BO 3 ) 4 , 12 BaTi(BO 3 ) 2 , 13 Ba 2 Mg(BO 3 ) 2 , 14 Ba 2 Mg(B 3 O 6 ) 2 , 15 Na 3 Ba 2 (B 3 O 6 ) 2 F, 16 AZn 4 (OH) 4 (C 3 N 3 O 3 ) 2 (A = Mg, Zn), 17 RbNH 4 (H 2 C 3 N 3 O 3 ) 2 ·2H 2 O, 18 Ba 3 (C 3 N 3 O 3 ) 2 , 19 Ba(NO 3 )Cl, 20 Cs 2 Pb(NO 3 ) 2 Br 2 , 21 (NH 4 ) 4 [B 12 O 16 F 4 (OH) 4 ], 22 Na[B 3 O 3 F 2 (OH) 2 ]·[B(OH) 3 ], 23 and A(H 3 C 3 N 3 O 3 )(NO 3 ); 24 (2) incorporating heteroanionic tetrahedral groups, such as [BO x F 4− x ]( x = 1–3), 25 [PO 3 F], 26,27 [PO 3 S], 28,29 and [SO 3 S]; 30,31 (3) adding d 0 metal cations with a second-order Jahn–Teller (SOJT) effect ( e.g. , Mo 6+ , V 5+ , and Nb 5+ ); 32–34 and (4) adding lone pair cations with stereoscopic activity ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…9 The birefringence phenomenon comes from structural anisotropy inside crystals. 10,11 Therefore, there are many strategies to design new birefringent crystal materials, including: (1) introducing planar π-conjugated groups (e.g., [BO 3 ], [B 3 O 6 ], [C 3 N 3 O 3 ] and [NO 3 ]); typical examples are Li 6 Zn 3 (BO 3 ) 4 , 12 BaTi (BO 3 ) 2 , 13 Ba 2 Mg(BO 3 ) 2 , 14 Ba 2 Mg(B 3 O 6 ) 2 , 15 Na 3 Ba 2 (B 3 O 6 ) 2 F, 16 AZn 4 (OH) 4 19 Ba(NO 3 )Cl, 20 Cs 2 Pb(NO 3 ) 2 Br 2 , 21 23 and A(H 3 C 3 N 3 O 3 )(NO 3 ); 24 (2) incorporating heteroanionic tetrahedral groups, such as [BO x F 4−x ](x = 1-3), 25 [PO 3 F], 26,27 [PO 3 S], 28,29 and [SO 3 S]; 30,31 (3) adding d 0 metal cations with a second-order Jahn-Teller (SOJT) effect (e.g., Mo 6+ , V 5+ , and Nb 5+ ); [32][33][34] and (4) adding lone pair cations with stereoscopic activity (e.g., Sb 3+ , Pb 2+ , Sn 2+ , and Bi 3+ ). 33,[35][36][37] In recent years, it has been found that π-conjugated [C(NH 2 ) 3 ] cations exhibit greater anisotropic polarizability and larger second-order polarizability than [BO 3 ] units.…”
Section: Introductionmentioning
confidence: 99%